Long-term effects of the targeting the ultra-poor program: A reproducibility and replicability assessment of Banerjee et al. (2021) - Julian Rose; Florian Neubauer; Jörg Ankel-Peters (RWI - Leibniz-Institut für Wirtschaftsforschung, 2024)
Banerjee, Duflo, and Sharma (BDS, 2021a) conduct a ten-year follow-up of a randomized transfer program in West Bengal. BDS find large effects on consumption, food security, income, and health. We conduct a replicability assessment. First, we successfully reproduce the results, thanks to a perfectly documented reproduction package. Results are robust across alternative specifications. We furthermore assess the paper's pre-specification diligence and the reporting in terms of extern. – – Banerjee, Duflo und Sharma (BDS, 2021a) führen eine zehnjährige Nachuntersuchung eines randomisierten Transferprogramms in Westbengalen durch. BDS finden große Auswirkungen auf Konsum, Ernährungssicherheit, Einkommen und Gesundheit. Wir führen eine Bewertung der Replizierbarkeit durch. Zunächst gelingt es uns, die Ergebnisse dank eines perfekt dokumentierten Reproduktionspakets zu reproduzieren. Die Ergebnisse sind robust gegenüber alternativen Spezifikationen. Darüber hinaus bewerten wir die Sorgfalt, mit der die Studie vor der Spezifikation erstellt wurde, und die Berichterstattung in Bezug auf die externen Daten.
Keywords: A1; O12; 330; Replicability; randomized controlled trial; transfer programs; research transparency